KEVALIDAN MODUL AJAR MATEMATIKA BERBASIS SENI VISUAL GEOMETRI UNTUK MENINGKAATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SEKOLAH DASAR DI KABUPATEN REJANG LEBONG - Novianti Mandasari; R. Angga Bagus Kusnanto (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to produce mathematics teaching modules based on visual arts geometry to improve the mathematical reasoning skills of Rejang lebong district elementary school students that are valid. The research method used is development research with a 4D development model, which consists of Difine, Design, Development and Desimate stages. The instrument used to answer the research objectives is in the form of a validity questionnaire, consisting of a linguist questionnaire, a material expert questionnaire, and a media expert questionnaire. The data in this study were analyzed using the Aiken V formula. Based on the results of the validity analysis of the three experts, an average value of 0.913 was obtained which was included in the interpretation category of Aiken's validity included in category V > 0.80 with very high information or can be said to be valid.